Extrakčně- spektrofotometrické stanovení fentanylu a jeho derivátů - Jelínková, Romana; Halámek, Emil; Kobliha, Zbyněk (Chemické listy, 2015)
Methods of determination of fentanyl, alfentanil, remifentanil and sufentanil were developed based on their ability to form coloured associates with acid dyes which can be extracted chloroform. Crocein Orange and Amido Black dyes produce the 1:1 and 2:1 associates at 485 nm and 626 nm, respectively.
Keywords: azosloučeniny; Alfentanil; alfentanil; Azo Compounds; Fentanyl; opioidní analgetika; Sufentanil; chemické techniky analytické; Analgesics, Opioid; chemická frakcionace; fentanyl; spektrofotometrie ultrafialová; Chemical Fractionation; Spectrophotometry, Ultraviolet; Chemistry Techniques, Analytical; sufentanil